2002
DOI: 10.1115/1.1416685
|View full text |Cite
|
Sign up to set email alerts
|

On the Improvement of Calibration Coefficients for Hole-Drilling Integral Method: Part I—Analysis of Calibration Coefficients Obtained by a 3-D FEM Model

Abstract: One of the important factors affecting the accuracy of stress values obtained from the hole-drilling method is the calibration coefficient. A three-dimensional model was established to determine the calibration coefficients for integral method. The constraint conditions and loading conditions during hole-drilling can be simulated more realistically with this method. With this new model, coefficients a¯i,j and b¯i,j could be determined within one computation procedure. The relationship between calibration coeff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 12 publications
1
13
0
5
Order By: Relevance
“…When a comparison is made with calibration coefficients obtained from other studies [8], similar trends and error rates were observed in the experimental calibration by different research works. It is therefore concluded that the coefficients calculated with the specified 3D FEM model are in agreement with the conventional coefficients of the incremental hole-drilling method.…”
Section: Determination Of Calibration Coefficientsmentioning
confidence: 62%
“…When a comparison is made with calibration coefficients obtained from other studies [8], similar trends and error rates were observed in the experimental calibration by different research works. It is therefore concluded that the coefficients calculated with the specified 3D FEM model are in agreement with the conventional coefficients of the incremental hole-drilling method.…”
Section: Determination Of Calibration Coefficientsmentioning
confidence: 62%
“…Using Hooke's law with plane stress approximation, the relieved radial strains at node ( , ), can be computed as: For the more complex case of a blind-hole, used in "thick" specimens (as it is the case for the rail application at hand), the relieved radial strain can be formally expressed by Eq. (4), with appropriate values for the calibration constants A and B (or ̅ and ̅ in most relevant literature) that are determined from experiments 6 and/or finite element models [7][8][9][10] . In typical finite element analysis, a structure under hydrostatic ( = ) and deviatoric ( = − ) stress state can be simulated to compute ̅ and ̅ , respectively.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…En el caso de tensiones residuales no uniformes y siguiendo el método integral, Aoh y Wei investigaron los coeficientes de calibración y para un amplio rango de espesores [Aoh02]. Definieron los espesores adecuados para placas delgadas y gruesas y propusieron los coeficientes de calibración para ciertos casos que después validaron experimentalmente [Aoh03].…”
Section: Espesor De Las Probetasunclassified
“…Esta estrategia lleva a resultados más precisos que la corrección propuesta. Otros autores solo dan los coeficientes para un diámetro [Aoh02], [Nau13b] y se ofrecen para calcular el valor para otros diámetros bajo petición [Beghini00 10].…”
Section: Diámetro Del Orificiounclassified
See 1 more Smart Citation